In Vitro Comparison of Passive and Active Clinical Proton Beams - Michaelidesová, Anna; Vachelová, Jana; Klementová, Jana; Urban, Tomáš; Pachnerová Brabcová, Kateřina; Kaczor, Stanislav; Falk, Martin; Falková, Iva; Depeš, Daniel; Vondráček, Vladimír; Davídková, Marie (International journal of molecular sciences, 2020)
Nowadays, the irradiation methodology in proton therapy is switching from the use of passively scattered beams to active pencil beams due to the possibility of more conformal dose distributions. The dose rates of active pencil beams are much higher than those of passive beams. The purpose of this study was to investigate whether there is any difference in the biological effectiveness of these passive and active irradiation modes. The beam qualities of double scattering and pencil beam scanning were measured dosimetrically and simulated using the Monte Carlo code. Using the medulloblastoma cell line DAOY, we performed an in vitro comparison of the two modes in two positions along the dose-deposition curve plateau and inside the Bragg peak. We followed the clonogenic cell survival, apoptosis, micronuclei, and γH2AX assays as biological endpoints. The Monte Carlo simulations did not reveal any difference between the beam qualities of the two modes. Furthermore, we did not observe any statistically significant difference between the two modes in the in vitro comparison of any of the examined biological endpoints. Our results do not show any biologically relevant differences related to the different dose rates of passive and active proton beams.
Keywords: apoptóza; Cell Line, Tumor; Micronucleus Tests; počítačová simulace; Apoptosis; lidé; Monte Carlo Method; neutrony; protonová terapie; pencil beam scanning; double scattering; Computer Simulation; cell survival; Linear Energy Transfer; lineární přenos energie; mikrojaderné testy; metoda Monte Carlo; proton therapy; histony; Histones; Cell Survival; Neutrons; viabilita buněk; Proton Therapy; nádorové buněčné linie; Humans